2018
DOI: 10.21548/39-2-2685
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the effectiveness and genetic positions of disease resistance loci in ‘Kishmish Vatkana’ (Ren1) and ‘Villard Blanc’ (Ren3 and Rpv3)

Abstract: This study aimed to validate the effectiveness and to genetically characterise the fungal disease resistance genes of 'Kishmish Vatkana' and 'Villard Blanc' in South Africa using microsatellite (SSR) markers and a Quantitative Trait Loci (QTL) approach. An F 1 'Sunred Seedless' × 'Kishmish Vatkana' cross was used to generate a partial linkage map for chromosome 13 known to harbour the Ren1 powdery mildew locus of 'Kishmish Vatkana'. The effectiveness of this locus was validated, explaining between 44.8% and 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The QTL results for this date show a QTL-region flanked by the markers UDV-116/GF15-30 and GF15-42/ScOR-A7 ( Figure 2 ). This region agrees with the previously published localization of locus Ren3 [ 16 , 23 ] and confirms it in this independent mapping study. The phenotypic scores of genotypes without any R -locus are shifted towards susceptible from the second scoring date onwards ( Figure 1 , 16-2 to 16-4) reflecting the developing PM epidemic and increasing infection pressure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The QTL results for this date show a QTL-region flanked by the markers UDV-116/GF15-30 and GF15-42/ScOR-A7 ( Figure 2 ). This region agrees with the previously published localization of locus Ren3 [ 16 , 23 ] and confirms it in this independent mapping study. The phenotypic scores of genotypes without any R -locus are shifted towards susceptible from the second scoring date onwards ( Figure 1 , 16-2 to 16-4) reflecting the developing PM epidemic and increasing infection pressure.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, the same research team showed the Ren3 QTL associated with marker UDV-116, which is located in the middle of chromosome 15. One could argue that if the marker density in the anterior part of chromosome 15 would have been increased, the QTL would have been possibly shifted further to the beginning of the chromosome [ 23 ]. Teh et al [ 24 ] also investigated the resistance Ren3 with a SNP based genetic map and phenotypic field data.…”
Section: Discussionmentioning
confidence: 99%